Acacia seed proteins: Low or high quality? A comprehensive review. Issue 1 (3rd December 2019) - Adiamo, Oladipupo Q.; Netzel, Michael E.; Hoffman, Louwrens C.; Sultanbawa, Yasmina
Abstract: The popularity of adding value to indigenous plant protein sources has increased due to the rise in the world population, high costs of animal protein as compared to plant proteins, and an increase in the consumer awareness of the nutritional and functional roles of dietary plant protein. Seeds of acacia plants (containing over 1, 350 species) have considerable amount of protein (18.25% to 35.5%) and nutritionists have shown great interest in assessing the quality and functionality of proteins from these protein‐rich plants. In this review, the overall nutritional and health‐promoting properties of acacia seed (AS) species are introduced. Extraction, quality, and functional properties of proteins from different AS species are discussed. Furthermore, anti‐nutritional components and protease inhibitors present in AS species and the effects of processing methods applied to lower the levels of anti‐nutrients are also discussed. Previous applications of AS in food formulations are highlighted. This review aims to provide updated findings that have been reported on AS proteins and to highlight areas for further studies in order to increase the utilization potential of the seeds.